Design and dynamic modelling of an ankle-foot prosthesis for humanoid robot - Alves, Joana (2017)
Bipedal locomotion is an important function of the human body, as it enables the mobility of the body through space, changing, therefore, the position of the person. Thus, a trauma (i.e limb amputation) or disease of the musculoskeletal system will affect not only the individual's locomotion but also the physical and psychological health, as well as the individual's social-interaction. Thereby, this work presents the 3D sketch of a transtibial prosthesis as well as a scale reduced model to be implemented on a biped robot (DARwIn-OP Robot). This model that will serve as case study to test the mechanism proposed for human ankle-foot prosthesis, is described throughout this paper. Also, for future system control implementation, a dynamic model of the prosthesis' main mechanism is described.